Identity, Gender, and Tracking The Reality of Boundaries for Veterinary Students - Vermilya, Jenny R. (Purdue University Press, 2022)
Using in-depth interviews with veterinary students, Identity, Gender, and Tracking: The Reality of Boundaries for Veterinary Studentsexplores the experience of enrollment in an educational program that tracks students based on the species of animals that they wish to treat. The identity of a veterinarian is one characterized by care; thus, students have to construct different definitions of care, creating a system of power and inequality. Tracking produces multiple boundaries for veterinary students, which has consequences not just for the veterinarian, but also for the treatment of animals. Written for administrators and students alike, Identity, Gender, and Tracking sheds light on how and why veterinary students construct their identities and end up in certain specializations.